Impact of gastrointestinal differences in veterinary species on the oral drug solubility, in vivo dissolution, and formulation of veterinary therapeutics - Marilyn N. Martinez; Mark G. Papich; Raafat Fahmy (International Association of Physical Chemists (IAPC), 2022)
Many gaps exist in our understanding of species differences in gastrointestinal (GI) fluid composition and the associated impact of food intake and dietary composition on in vivo drug solubilization. This information gap can lead to uncertainties with regard to how best to formulate pharmaceuticals for veterinary use or the in vitro test conditions that will be most predictive of species-specific in vivo oral product performance. To address these challenges, this overview explores species-specific factors that can influence oral drug solubility and the formulation approaches that can be employed to overcome solubility-associated bioavailability difficulties. These discussions are framed around some of the basic principles associated with drug solubilization, reported species differences in GI fluid composition, types of oral dosage forms typically given for the various animal species, and the effect of prandial state in dogs and cats. This basic information is integrated into a question-and-answer section that addresses some of the formulation issues that can arise in the development of veterinary medicinals.